The representation of touristification in media through mapping: the case of Malaga. - Chamizo-Nieto, Francisco José; Nebot-Gómez de Salazar, Nuria; Rosa-Jiménez, Carlos; Castro-Martínez, Andrea (Transinformação, 2023)
The touristification agenda has had considerable representation in the media in recent years because of tourism specialisation in cities. Existing literature has focused on using content analysis; however, previous content analyses have not typically been mapped. The main objectives were to conduct an in-depth measurement of urban tourism issues covered in the press and the stakeholders involved, but spatially. To show the spatial representation of touristification, Malaga is used as a case study as it is an emerging tourist city. The article analyses the content of 166 news items on touristification in Malaga published in the most-read local newspapers up to and including the year 2020. Data categorised were mapped to assign a sum of news articles about touristification issues at neighbourhood level. Density mapping shows a common pattern for each category: an over-representation of the city centre and a reduction in the number of news items per neighbourhood as we move away from the old town. A Pearson correlation coefficient shows a high spatial correlation between neighbourhoods in the press with several citizen initiatives geolocated on them. A spatial analysis shows where the negative impacts of tourism intensification happen, which may serve as a basis for the local administrations to develop an urban policy to safeguard residential use in those neighbourhoods under tourism pressure. This work serves as a basis for new research on touristification: the addition of case studies to identify common urban patterns and the definition of a social conflict index through the geolocation of the stakeholders involved.
Keywords: Turismo - Málaga; Gentrification; Geographic Information System; Media content analysis; Overtourism; Stakeholders; Tourism intensification